The Implications of locally managed SNSs on e-government implementation and community building - Inri Inggrit Indrayani (Jurnal Studi Pemerintahan, 2023)
The local government of Surabaya builds Social Network Sites (SNSs) in interacting with citizens. In addition, at the sub-local level, social communication institutions located in each urban village manage SNSs as well. This research aims to find the implications of the use of locally managed SNSs in each urban village in Surabaya. The research used a qualitative approach and case study. The data was collected by interviewing 15 informants and observing digital artifacts on local SNSs in several urban villages. This research found that the use of locally managed SNSs in urban villages has implications for strengthening e-government implementation, firstly, to provide a variety of services and public information about the potential and strengths of each urban village; secondly, to activate and increase public capacity in each urban villages in the digitalization. Another implication is on community building by maintaining stakeholder engagement and building ‘we feeling’ in the public of each urban village. This research provides insight into the management and use of SNSs in sub-local contexts both for the reinforcement of e-government implementation and the maintenance of social capital in a developing country that seeks to maintain democratization stability.